SUSUT PANEN DAN PASCAPANEN PADI GOGO VARIETAS BURUNGAN (Studi Kasus di Desa Molonggota Kecamatan Gentuma Raya Kabupaten Gorontalo Utara) - Yulinda Tatipang; Lady Ch. E. Lengkey; Handry Rawung (Universitas Sam Ratulangi, 2015)
ABSTRACT Rice is the most exerted food crop commodity in Indonesia. Rice production has continuously been increased in order to support food security policy. Improvement of cultivation technology has been proved to increase rice production significantly. The aim of this study is to the losses of harvest and postharvest losses including harvest lost to threshing.Â Â This research was done from February to May 2015, in Pagulage cape, Molonggota village, subdistrict Gentuma Raya , North Gorontalo.The study of this research showed that the average of harvest lossed was 1,94 %, temporary hoarding lossed was 0,54 %, binding with transport lost was 1,13 % and fall of lost was 2 % with total cost was 5,61 %. This research showed that the highest lost was in fall of lossed and the lowest cost was in temporary hoarding lost that containing water about 17 %. The improvement of rice postharvest technology should in corporate human reseurse abily and introduced the postharvest technology to the farmer should be done.